World Rabies Day – a decade of raising awareness. Issue 1 (December 2016) - Balaram, Deepashree; Taylor, Louise; Doyle, Kim; Davidson, Elizabeth; Nel, Louis
Abstract World Rabies Day was set up in 2007 to raise global awareness about rabies, to provide information on how to prevent the disease in at-risk communities and support advocacy for increased efforts in rabies control. It is held annually on September 28th, with events, media outreach and other initiatives carried out by individuals, professionals, organisations and governments from the local to the international level. The Global Alliance for Rabies Control coordinates World Rabies Day, amplifying the campaign's reach through the provision of a central event platform and resources to support events across the world, the promotion of messages through key rabies stakeholders, and the implementation of specific activities to highlight particular issues. Over the last decade, more than 1, 700 registered events have been held across the world and shared with others in the global rabies community. Events in canine rabies endemic countries, particularly in Africa and Asia, have increased over time. Beyond the individual events, World Rabies Day has gained the support of governments and international agencies that recognise its value in supporting existing rabies control initiatives and advocating for improvements. As the rabies landscape has changed, World Rabies Day remains a general day of awareness but has also become an integral part of national, regional and global rabies elimination strategies. The global adoption of 2030 as the goal for the elimination of rabies as a public health threat has led to even greater opportunities for World Rabies Day to make a sustainable impact on rabies, by bringing the attention of policy makers and donors to the ongoing situation and elimination efforts in rabies-endemic countries.